ANALISIS STRATEGI PERSONAL BRANDING ERIKA RICHARDO PADA AKUN TIKTOK@ERIKARICHARDO - Dwi Yanti Br Pinem, Sabrina; Mustika Chairil, Augustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
TikTok has become one of the most popular social media platforms for content creators to build their personal branding. Erika Richardo is recognized for her distinctive painting content created on various unique media. This study aims to analyze Erika Richardo's personal branding strategy on her TikTok account, @erikarichardo, using Hubert K. Rampersad's Authentic Personal Branding theory. This research employed a descriptive qualitative approach with a content analysis method. Data were collected through documentation and observation of 30 TikTok videos with high engagement rates. The findings indicate that Erika Richardo's personal branding is reflected through the dimensions of authenticity, integrity, specialization, authority, distinctiveness, visibility, persistence, goodwill, and performance. Among these, authority and distinctiveness emerged as the most dominant aspects, reflected in her large-scale creative projects, collaborations, and consistent presentation of paintings on unique media. In addition, the Unique Painting Media category represents Erika's primary identity as both an artist and a content creator. The study concludes that Erika Richardo's personal branding is built through competence, creativity, and consistency in producing authentic content on TikTok.